Portraits of Deburau in Janin's Deburau, l'histoire du théâtre à quatre sous - Nye, E (Johns Hopkins University Press, 2019)
Jean-Gaspard Deburau was one of the most famous faces of nineteenth-century theatre. He performed the Pierrot role at the Théâtre des Funambules in Paris from 1816 until his death in 1846. His fame was due in part to the efforts of writers such as Jules Janin whose biography in 1832 was extensively illustrated with portraits of the mime actor. The intermedial relationship between the text and the images is evidence of a characteristically Romantic concept of the art of portraiture based on intuition and imagination as much as historical fact. Janin's book contributed to the transformation of Deburau into a contemporary cultural icon.